Mesencephalic astrocyte-derived neurotrophic factor (MANF) protects against Aβ toxicity via attenuating Aβ-induced endoplasmic reticulum stress - Shengchun Xu; Zemin Di; Yufeng He; Runjie Wang; Yuyang Ma; Rui Sun; Jing Li; Tao Wang; Yujun Shen; Shengyun Fang; Lijie Feng; Yuxian Shen (Journal of Neuroinflammation, 2019)
Abstract Background Extracellular accumulation of amyloid β-peptide (Aβ) is one of pathological hallmarks of Alzheimer’s disease (AD) and contributes to the neuronal loss. Mesencephalic astrocyte-derived neurotrophic factor (MANF) is an endoplasmic reticulum (ER) stress-inducible neurotrophic factor. Many groups, including ours, have proved that MANF rescues neuronal loss in several neurological disorders, such as Parkinson’s disease and cerebral ischemia. However, whether MANF exerts its protective effect against Aβ neurotoxicity in AD remains unknown. Methods In the present study, the characteristic expressions of MANF in Aβ1–42-treated neuronal cells as well as in the brains of APP/PS1 transgenic mice were analyzed by immunofluorescence staining, qPCR, and Western blot. The effects of MANF overexpression, MANF knockdown, or recombination human MANF protein (rhMANF) on neuron viability, apoptosis, and the expression of ER stress-related proteins following Aβ1–42 exposure were also investigated. Results The results showed the increased expressions of MANF, as well as ER stress markers immunoglobulin-binding protein (BiP) and C/EBP homologous protein (CHOP), in the brains of the APP/PS1 transgenic mice and Aβ1–42-treated neuronal cells. MANF overexpression or rhMANF treatment partially protected against Aβ1–42-induced neuronal cell death, associated with marked decrease of cleaved caspase-3, whereas MANF knockdown with siRNA aggravated Aβ1–42 cytotoxicity including caspase-3 activation. Further study demonstrated that the expressions of BiP, ATF6, phosphorylated-IRE1, XBP1s, phosphorylated-eIF2α, ATF4, and CHOP were significantly downregulated by MANF overexpression or rhMANF treatment in neuronal cells following Aβ1–42 exposure, whereas knockdown of MANF has the opposite effect. Conclusions These findings demonstrate that MANF may exert neuroprotective effects against Aβ-induced neurotoxicity through attenuating ER stress, suggesting that an applicability of MANF as a therapeutic candidate for AD.